2014
DOI: 10.1371/journal.pone.0086322
|View full text |Cite|
|
Sign up to set email alerts
|

Aggregation of Human Recombinant Monoclonal Antibodies Influences the Capacity of Dendritic Cells to Stimulate Adaptive T-Cell Responses In Vitro

Abstract: Subvisible proteinaceous particles which are present in all therapeutic protein formulations are in the focus of intense discussions between health authorities, academics and biopharmaceutical companies in the context of concerns that such particles could promote unwanted immunogenicity via anti-drug antibody formation. In order to provide further understanding of the subject, this study closely examines the specific biological effects proteinaceous particles may exert on dendritic cells (DCs) as the most effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 29 publications
7
138
3
1
Order By: Relevance
“…Although nowadays the use of humanized or fully-human biodrugs has greatly contributed to reduce this risk, immunogenicity associated to the aggregation of biodrug molecules and other factors is still a major concern for the optimum exploitation of these modern drugs [296,297]. The association between biodrug molecules upon injection has been thought to be a natural way to enhance antigen processing and presentation in the cells [298,299]. On the other hand, the presence of impurities could also be part of the problem.…”
Section: The Next Challenge In Immunomodulation: Overcoming Antidrmentioning
confidence: 99%
“…Although nowadays the use of humanized or fully-human biodrugs has greatly contributed to reduce this risk, immunogenicity associated to the aggregation of biodrug molecules and other factors is still a major concern for the optimum exploitation of these modern drugs [296,297]. The association between biodrug molecules upon injection has been thought to be a natural way to enhance antigen processing and presentation in the cells [298,299]. On the other hand, the presence of impurities could also be part of the problem.…”
Section: The Next Challenge In Immunomodulation: Overcoming Antidrmentioning
confidence: 99%
“…Product properties that affect immunogenicity include molecular structures, post-translational modifications, impurities, immunomodulatory properties and aggregation [7,9,57]. Among these, aggregation of TPP carries particular concern, as it occurs under some conditions with many TPP and several studies have identified associations between aggregates and increased propensity for immunogenicity [51,[81][82][83][84][85][86]. Compared with non-aggregated forms, higher immunogenicity in mice has been observed for aggregates generated under different stress conditions for various TPPs, such as human interferon alpha2b [87][88][89], human mAbs [90][91][92], human epoetin alfa [83], human Factor VIII [93,94], human interferon beta [95], and murine growth hormone [96].…”
Section: Factors That Influence Immunogenicitymentioning
confidence: 99%
“…Compared with non-aggregated forms, higher immunogenicity in mice has been observed for aggregates generated under different stress conditions for various TPPs, such as human interferon alpha2b [87][88][89], human mAbs [90][91][92], human epoetin alfa [83], human Factor VIII [93,94], human interferon beta [95], and murine growth hormone [96]. The detailed mechanisms of aggregate-induced immunogenicity are still unknown, but it has been observed that aggregation enhances antigen uptake, increases the total amount of peptides associated with MHC II molecules, and increases danger signals to maturate dendritic cells and activate T cells [52,86,91,97,98]. Therefore, aggregates could contribute to increased immunogenicity through enhancing antigen processing and presentation in the T cell-dependent pathway.…”
Section: Factors That Influence Immunogenicitymentioning
confidence: 99%
“…15 Specific high-affinity neutralizing IgG1 and IgG4 antibody responses to rhEPO indicate T-cell-dependent isotype switching. 2,16 Because in vitro T-cell assays have been successfully used to evaluate the mechanism of immune responses to biotherapeutics, [5][6][7][8][9] vaccines, 17,18 and self-antigens in vitro, 19,20 we investigated in vitro T-cell responses to experimentally heat-induced rhEPO aggregates, and tungsteninduced rhEPO aggregates in clinical lots associated with rhEPOneutralizing antibodies and PRCA. Furthermore, we studied ex vivo T-cell recall responses of patients treated with rhEPO without PRCA, and of patient P1 who developed PRCA after treatment with a clinical batch with elevated levels of tungsten and aggregates.…”
Section: Introductionmentioning
confidence: 99%